The teaching profession in crisis: The decrease of enrollment in normal schools of Mexico - Jihan García-Poyato Falcón; Graciela Cordero Arroyo (Arizona State University, 2019)
The decrease in interest in pursuing a teaching career is an international phenomenon. In the case of Mexico, periods of decline in interest in entering normal schools are associated with changes in the working conditions of teachers. The objective of this article is to present the results of a research work on the declining enrollment of the bachelor of arts in primary education (BAPE) as a consequence of the decrease in the number of applicants to enter this profession in Mexico. This exploratory study comprised two phases. In the first one, a revision of the federal policies regarding the teaching career and entrance to the normal schools is made. In the second phase, the statistics of the BAPE were analyzed. In relation to the applicants, a national reduction of 57% was found from 2011-2012 to 2017-2018, while enrollment shows a national declining of 17% from 2011-2012 to 2018-2019. In view of the clear and abrupt reduction of interest towards teacher education in a normal school, it is necessary to deepen the identification of the causes to implement national strategies that allow for reversing this phenomenon.